Enhancing Awareness of the Role of the Sharia Supervisory Board Amid the Digitalization Revolution in Sharia Financial Products - Mirza, Azrul Azlan Iskandar; Mutafarida, Binti; Saka, Dijan Novia; Anam, Choiril; Zainuddin, Moch.; Zunaidi, Arif; Sariati, Ning Purnama (Welfare : Jurnal Pengabdian Masyarakat, 2024)
This community service aims to increase understanding of the role of the Sharia Supervisory Board (DPS) in facing the digitalization revolution of sharia financial products. The method used is service learning, where active interaction between students and the community is involved in understanding the DPS concept. Through needs mapping, program planning, and implementation involving competent resources, this activity integrates learning and service to achieve these goals. The evaluation results show an increase in participants' understanding, both regarding DPS concepts and digital literacy, as a positive impact of this activity. Therefore, this service makes a positive contribution to sharia financial literacy in the digital era and empowers the community to face changes in the sharia financial industry.